Asian Australian Identities: Embodiments and Inhabitations. (1st November 2020) - Chakraborty, Mridula Nath; Walton, Jessica
ABSTRACT: Theories of embodiment recognise the critical politics of emplacement associated with the body, as well as its situatednesses in, and as, sites of performance. What happens when such locations shift due to crossings in terms of bloodlines, caste, class, family, gender, nation, race, region, religion, ability and sexuality, among others? How do embodiments that cross perimetres of categories inhabit their place and being, both in the Bourdieusian sense of habitus as well as that of phenomenologists like Merleau-Ponty? Following from these questions, we examine and explore the ways in which Asian Australian land/mind/body scapes and embodiments are made meaningful in changing contexts of communities and crossings, how habitations over space, time and history challenge our ideas of being and body. The theme of embodiments and inhabitations reflects on past practices that have shaped, and continue to shape, the lives of Asian Australians, and to interrogate these practices while also moving beyond them to generate new knowledge. Our analyses push the boundaries of notions of home, rootedness, belonging and place, and past and present: we re-invent, instead of simply responding to the limited ways in which Asian Australians have been hitherto conceptualised and their experiences understood in dominant discourses.